THU0525 A Prospective, Multi-Centre, Prevalence-Based Cost-of-Illness Study of RA in the UK. Relative Costs of Biologics and Orthopaedic Surgery in Established Disease. (23rd January 2014) - Nikiphorou, E.; Morris, S.; MacGregor, A.; Cooper, N.; Chipping, J.; Symmons, D.; Young, A.
Abstract : Background: Cost-of-illness (COI) studies help identify the economic consequences of a disease like Rheumatoid Arthritis (RA) and are directly relevant to health service decisions and policy- planning. Most COI studies are based on early disease or are cross-sectional. Those confined to early disease stages may fail to accurately capture all disease costs. Orthopaedic surgery and consequent inpatient stays are typically required later in the course of RA. Objectives: To undertake a prevalence-based COI study of established RA from a UK NHS perspective. Methods: Non-surgical resource use data were taken from the Norfolk Arthritis Register (NOAR), a long-term primary-care based prospective cohort of patients with inflammatory polyarthritis of which RA is a major subset. The first health economic study was conducted in this group in 2002; these patients were traced in 2009 and invited to participate in a longitudinal questionnaire based study designed to capture health costs using previously validated instruments and covering a 6 month window. Only patients classified using the ACR criteria as having RA (n=64) were included in the COI study. Reference cost data for primary care/hospital costs were provided by the Personal Social Services Research Unit and drug costs by the British National Formulary all in 2009 British pounds(£). Due to limited patient numbers undergoing orthopaedic surgery in the COI study, a reference group was identified from the Early Rheumatoid Arthritis Study (ERAS: recruited 1986-1999, 9 centres) who required orthopaedic surgery during the same health-economic study period as NOAR (n=34). ERAS data were cross-validated with national data from Hospital Episode Statistics and the National Joint Registry. Surgical costs were based on individual ERAS procedures, following which the mean cost per surgery was multiplied by the number of patients requiring surgery in NOAR (n=2) which was the same proportion as patients having surgery in ERAS during the study period (3%). Surgical reference costs were provided by the Department of Health. NOAR medical costs were calculated as the sum of products of the quantity of resources used and the unit cost of the relevant resource. Results: The mean annual cost per RA patient was £3, 614/€4033 (range £55-6958/€61-7765). Non-surgical costs were categorised into primary care (11%), hospital outpatient and day care admissions (26%) and medications (54%), 90% due to biologic drugs. Surgical costs represented 10% of the total, including a range of minor (e.g. soft-tissue), intermediate (e.g. excision arthroplasties) and major interventions (e.g. total joint arthroplasties). The mean cost per surgical procedure was £5, 579/€6226. Based on the estimated UK population with RA (404, 100), the total annual cost of RA was estimated to be £1.46/€2 billion. Conclusions: This COI study is unique in that it undertakes a detailed examination of both direct medical and surgical costs in established RA. It highlights that RA continues to pose a substantial economic burden on the NHS and also confirms the common perception that biologics are having a major impact on the cost of managing established RA. Disclosure of Interest: None Declared